The estimation of the convergence rate for maxima of random variables vectors - Dindienė, Lina; Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2010)
Linearly normalized maxima of independent and identically distributed random vectors is presented in this work. We’ve obtained nonuniform estimate of convergence in case when normalization is linear. For clearness there is given an example is this paper. Transfer theorem was aplied.
Keywords: stochastic maxima; transfer theorem; rate of convergence